Nursing professionals' perception of parents' hesitation regarding children's vaccination - Andrade, Nádia Luany (2025)
Immunization is essential in public health, as it prevents potentially fatal diseases and complications. One of the factors that explain the drop in childhood immunization coverage is vaccine hesitancy. Objective: To identify the perception of nursing professionals about the factors that prevent parents from keeping their children's vaccination records up to date. Method: Qualitative and descriptive study. For data analysis, we chose to base the research on Roy's Adaptation Theory. Results: The research included 7 female nursing professionals who work in vaccination rooms, aged between 35 and 50 years. Among the participants, 2 had technical training in Nursing, and 5 had a degree in Nursing. The data collection instrument was a questionnaire, and after data analysis, two thematic categories emerged and were discussed: “The influence of Fake News on children's immunization” and “Parents' and caregivers' fear of adverse reactions after vaccination”. Final considerations: It is essential that health professionals implement effective educational strategies, promote clear and consistent communication from health authorities, and offer emotional and psychological support to overcome barriers associated with immunization.